Patients' acceptance of medical photography in a French adult and paediatric dermatology department: a questionnaire survey. (13th August 2013) - Hacard, F.; Maruani, A.; Delaplace, M.; Caille, A.; Machet, L.; Lorette, G.; Samimi, M.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Despite the increasing use of medical photography, no study regarding patients' perceptions of photography in dermatology has been undertaken to date. What does this study add? We evaluated patients' perceptions of medical photography in a French adult and paediatric dermatology department to assess their acceptance of several practical aspects of medical photography and their opinions about the financial and legal implications.